Dynamic surface control for electro-hydraulic servo cylinder system - Nghiêm Xuân, Thước; Trần Đức Thuận; Nguyễn Việt Anh; Nguyễn Xuân Quỳnh (Journal of Military Science and Technology, 2024)
Electro-hydraulic systems are widely used in industrial production due to their high power-to-weight ratio, but their heavy-duty nature causes electro-hydraulic systems to endure large disturbance forces even when the actuator slight movement, especially in mobile machines and a system of multiple actuators. Dynamic surface control based on the backstepping method is applied to avoid the derivative explosion phenomenon when calculating the derivative of the virtual control input, which greatly reduces the computational complexity of the system. To verify the effectiveness of the proposed controller, the proportional integral controller is designed to compare with the dynamic surface control using the Backstepping technique and the comparison results show that The proposed controller has more accurate trajectory tracking performance.